Local Participation in Community Based Development Projects in Ghana - Aryeh-Adjei, A.A.; Anang, S.A.; Osei-Adusah, D. (International Journal of Social Ecology and Sustainable Development, 2022)
The study critically analyses how the local people in Ga West municipality perceive local participation and socio-cultural factorsthat influence local participation. The study used the mixed method design. The lottery method of the simple random sampling technique coupled with Neuman and Neuman’s recommendation on random convenience sampling were used to sample and collect data from 187 respondents. The study revealed that local participation providesthe local people employment avenues. It wasrevealed that developmental projects brought to their communities do not allow the local people to be involved at the planning and implementation phases. The study further revealed that women were of the opinion that projects brought to them were not feminine enough and did not build their capacity. Education,social cohesion, peace, and stability were among some of the sociocultural factors that influence participation. The study again recommended that every community member should participate, regardless of their gender, ethnic group, or socio-cultural differences.
Research Article
Keywords: Community; Community-Based Development Projects; Local Participation; Stakeholder